(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Children are restless, their desire to explore the world around them sometimes ends in tears. Abrasions, bruises, cuts, burns are not the whole list of injuries that are often found in children. Injuries to the oral cavity are also not uncommon and no less diverse. In addition to fractures and dislocations of teeth, tears, cuts and abrasions of the soft tissues of the oral cavity are often found in the practice of pediatric dentists.